Harmonic Analysis In Multilevel Inverter Using Hybrid Pwm Technique - Tiong, Soon Hung (2022)
In earlier decade, the Multilevel Inverter (MLI) has only able to perform on conversion of DC to DC but in this new era, the multilevel inverter is widely being used to gained the desired output from DC voltage to AC voltage source. The objective of this research work is to design and simulate multiple Hybrid Pulse Width Modulation (PWM) technique for multilevel inverter and then analyse its performance by compare it with the conventional phase disposition (PD) PWM technique in terms of harmonic (THD) percentage. This research work is develop using MATLAB SIMULINK with 200V of DC source that implement the 18 types of hybrid PWM from some common type of pulse width modulation (PWM) technique to improve the output voltage by decrease the Harmonic Distortion (THD) of the multilevel inverter which is the cascaded H-bridge multilevel inverter (CHMI) is being used. Due to some of the conventional PWM technique are still causing an extra loss of power cause by high harmonic distortion value. Therefore, Hybrid PWM techniques are able to mitigate this problem. The result from the research work is compared in terms of percentage of THD values. Overall, all of the other method that has been developed was all below 5% of standard limit. However, two of the methods that generated lowest THD values at 0.88% are PS-PD PWM and PS-POD PWM hybrid methods in high carrier frequency bands switching technique.